A case study of inclusion of rural populations in research: Implications for science and health equity - Devon Noonan; Wendy K. K. Lam; James Goodrich; Sydney Sullivan; Keisha Bentley‐Edwards; Dwight Koeberl; Anushka Palipana; F. Joseph McClernon (Wiley, 2024)
Abstract Prior research highlights that rural populations have been historically underrepresented/excluded from clinical research. The primary objective of this study was to describe the inclusion of rural populations within our research enterprise using Clinical Research Management System demographic information at a large academic medical center in the Southeast. This was a cross‐sectional study using participant demographic information for all protocols entered into our Clinical Research Management System between May 2018 and March 2021. Descriptive statistics were used to analyze the representation of rural and non‐rural participants and demographic breakdown by age, sex, race, and ethnicity for our entire enterprise and at the state level. We also compared Material Community Deprivation Index levels between urban and rural participants. Results indicated that 19% of the research population was classified as rural and 81% as non‐rural for our entire sample, and 17.5% rural and 82.5% urban for our state‐level sample. There were significant differences in race, sex, and age between rural and non‐rural participants and Material Community Deprivation Indices between rural and non‐rural participants. Lessons learned and recommendations for increasing the inclusion of rural populations in research are discussed.